Rippling : How Social Entrepreneurs Spread Innovation Throughout the World - Schwartz, Beverly (San Francisco Jossey-Bass, 2012)
"Drawing on the knowledge and experience of working with hundreds [of] the world's top social change leaders in all fields, Beverly Schwartz presents a model for change based on five proven principles that any individual leader or organization can apply to bring about deep, lasting and systematic change. Rippling shows how to activate the type of change that is needed to address the critical challenges that threaten to destroy the foundations of our society and planet in these increasingly turbulent times"--Publisher's description.
Include Epilogue, Notes and Index
Keywords: Social change -- Social entrepreneurship -- Business